The relative contribution of road bicycle components on vibration induced to the cyclist - Lepine, J.; Champoux, Y.; Drouet, J.-M. (Sports Engineering, 2015)
Improving comfort in road bicycle design is a paramount concern for cyclists, who are affected by the vibrations caused by constant contact with the road surface. The cycling community has deployed many efforts in the attempt to understand and improve bicycle comfort. However, these attempts have been focused on specific components such as the fork, frame and wheels without knowing their relative influence on vibration induced to the bicyclist (VIB). The objective of this paper is to assess the relative contribution of bicycle components on the VIB at the cyclist`s hands and buttocks. A factorial design test comparing the VIB in acceleration, force and power of different bicycle components has already shown that the handlebar and fork are the preponderant components for the VIB measured at the cyclist`s hands. At the buttocks, the preponderant components are the wheels and frame.